The Royal Commision Report for strategic management and improvement of the Royal Malaysian Police - A. Kadir, Nadrah; Jusoff, Kamaruzaman (Canadian Research & Development Center of Sciences and Cultures, 2009)
The focus of this paper is on the Royal Malaysian Police (RMP) where the issues in improving the RMP along with its problems from the perspective of strategic management in the public sector based on three important themes i.e., strategy, implementation and politics were addressed. The discussion draws substantially from the Report of the Royal Commission to Enhance the Operation and Management of the Royal Malaysia Police (2005) [hereafter RCR] and the analysis was guided by the framework presented by Kelman (1987) and Moore (1995). For any improvement to take place, the problems must first be identified. Based on the problems of the RMP identified by the Royal Commission (RC), suggestions for improvement will be provided. This paper starts by looking at the strategy of the RMP. This is followed by the second section which focus on the implementation part and the concluding section provides the challenges facing the RMP with regard to the politics.